1961
DOI: 10.1002/zaac.19613130110
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis der Lithiumaluminate. I. Über eine neue Modifikation des LiAlO2

Abstract: Beim Tempern eines äquimolaren Gemisches von Li2CO3 und α‐Al2O3 bei 600° entsteht eine Tieftemperaturform des LiAlO2 mit der Dichte 3,38 g · cm−3, die sich oberhalb 600°C langsam und anscheinend irreversibel in die bekannte Hochtemperaturform umlagert. T‐ und H‐LiAlO2 stehen wahrscheinlich im gleichen Verhältnis zueinander wie α‐ und β‐NaFeO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

1962
1962
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 3 publications
3
16
0
Order By: Relevance
“…It is well known that Li 2 O and Al 2 O 3 can form stable a-LiAlO 2 with the a-NaFeO 2 structure at temperatures below 6001C (8)(9)(10). The intercalation of a-LiAlO 2 gives a voltage of B5 V vs Li/ Li + , which is higher than other lithium transition-metal oxides.…”
Section: Introductionmentioning
confidence: 97%
“…It is well known that Li 2 O and Al 2 O 3 can form stable a-LiAlO 2 with the a-NaFeO 2 structure at temperatures below 6001C (8)(9)(10). The intercalation of a-LiAlO 2 gives a voltage of B5 V vs Li/ Li + , which is higher than other lithium transition-metal oxides.…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown theoretically [11,12] and experimentally [13,14] that Al as a substitutive substitution transition metal cation increases the cell voltage. Moreover, LiAlO 2 is stable in the α-NaFeO 2 structure at temperatures below ∼600 • C [15] and it has a stabilizing effect on the structure as reported for monoclinic LiAl y Mn 1−y O 2 [16]. Its low cost and low density makes LiAlO 2 attractive as a constituent intercalation compound.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, the corresponding numbers of phonon vibrational modes are 12, three of them are acoustic modes and 9 of remainder are optical modes. Since ␣-LiAlO 2 is in a rhombohedral symmetry structure with space group R-3 m [5], the corresponding point group is −3m. According to Group-theoretical analysis [34], the irreducible representations of normal modes at the center of the BZ can be expressed as…”
Section: Dynamical Propertiesmentioning
confidence: 99%
“…It has been reported that LiAlO 2 has at least four different phases, the hexagonal ␣-phase [5,6], the orthorhombic ␤-phase [7], the tetragonal ␥-phase [8], and the tetragonal ␦-phase [9]. It is thought that the ␥-LiAlO 2 powder has been considered to be the most stable form and is commonly used as the electrolyte material because of its stability at high temperature [10].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation